Xanthogranulomatous cholangitis mimicking cholangiocarcinoma: Case report and review of literature. (April 2022) - Zhang, Jenny Q.; Truong, Lance; Pan, Jason; Yakirevich, Evgeny; Hyder, Sarah M.; Beard, Rachel E.
Abstract: Introduction: Xanthogranulomatous cholangitis is an extremely rare diagnosis and is believed to be an extension of xanthogranulomatous cholecystitis, a benign inflammatory process characterized by lipid-laden foamy macrophages (called "xanthoma cells") occurring in a background of chronic inflammation consisting of lymphocytes, plasma cells, and eosinophils. Here, we report a case of xanthogranulomatous cholangitis mimicking cholangiocarcinoma. Case presentation: A 72 year old male with history of recurrent cholangitis had preoperative workup highly suggestive of intrahepatic cholangiocarcinoma. He underwent right hepatectomy and portal lymphadenectomy, with pathology showing xanthogranulomatous cholangitis, with no evidence of malignancy. Interestingly, the patient did not have xanthogranulomatous cholecystitis. Discussion: We reviewed the current literature on xanthogranulomatous cholangitis, and identified only 14 previously reported cases. In our case series, there were six female and eight male patients. Among the 14 patients, 11 presented to the hospital with jaundice. Twelve patients had preoperative workup concerning for malignancy. The diagnosis of xanthogranulomatous cholangitis was confirmed through pathology in 13 patients, and through endoscopic ultrasound biopsy in one patient. In our review, seven patients had associated xanthogranulomatous cholecystitis, three patients had an isolated case of xanthogranulomatous cholangitis, and four patients had unknown status. Our patient is the fourth case of isolated xanthogranulomatous cholangitis without xanthogranulomatous cholecystitis. Conclusion: Xanthogranulomatous cholangitis is a very rare phenomenon that can lead to benign strictures of the bile ducts, especially in the setting of recurrent cholangitis. It can mimic malignancies, such as cholangiocarcinoma, and should be considered in the differential diagnosis. Highlights: Xanthogranulomatous cholangitis is an extremely rare inflammatory process. It involves lipid-laden macrophages of the bile duct. Patients with xanthogranulomatous cholangitis frequently present with jaundice. It can mimic malignancies, including bile duct, liver, gallbladder, and pancreatic cancers. It should be included in the differential diagnosis of biliary abnormalities